2022
DOI: 10.3389/fmats.2022.880702
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependence Corrosion Behavior of Ti6Al4V in the Presence of HCl

Abstract: Ti alloys have been widely used in biomedical field due to good compatibility and corrosion resistance. However, corrosion-related failures of implanted Ti devices and prostheses have been regularly reported within the medical literature. The corrosion of Ti alloys has attracted much attention in vivo and in vitro. In the current study, the corrosion behavior of Ti6Al4V alloy was investigated using surface analysis and electrochemical tests. Corrosion of Ti6Al4V in 2 M hydrochloric acid is temperature dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In the present study, the content of V was comparable in both abutments. Hence, other authors reported that this element (a known β-stabilizer) increased the dissolution (in H 2 SO 4 ) of the oxide layer due to the defects and ionic conductivity, which increased when the alloying elements (i.e., V) diffused into the oxide layer [19,48]. Consequently, the corrosion of the alloy increased.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the present study, the content of V was comparable in both abutments. Hence, other authors reported that this element (a known β-stabilizer) increased the dissolution (in H 2 SO 4 ) of the oxide layer due to the defects and ionic conductivity, which increased when the alloying elements (i.e., V) diffused into the oxide layer [19,48]. Consequently, the corrosion of the alloy increased.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the efficiency of the passivating layer is reduced [47]. Interestingly, it was suggested that the detrimental effect of Al (inducing corrosion) in HCl might dominate over other factors [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieval studies show evidence of chemically induced corrosion of the Ti-6Al-4V 𝛼 phase and recently published in vitro studies show that 𝛼 may be targeted for preferential dissolution. [7,9,54] More in vitro work is needed to confirm this hypothesized in vivo mechanism. Future studies will evaluate the cyclic effect of cathodic activation and inflammatory species on the oxide capacitance and R p .…”
Section: Discussionmentioning
confidence: 99%
“…For Ti6Al4V, the total volume and weight loss were found to be similar, whereas Ti-E ano possesses higher corrosion mass loss (Kc) and higher oxygen concentration than Ti-E cath . The applied anodic potential (500 mV) is considered a corrosion-accelerated condition [28,34,48], which can explain the fact that Ti-E ano showed the highest Kc among all potentials. However, 500 mV is in the range of the repassivation potential for Ti6Al4V [30], and it was reported that the thickness of the passive film created on Ti alloys is proportional to the applied potential [4952], meaning that the regrowth of the passive layer is encouraged under anodic conditions, which can be supported by the high oxygen concentration from EDS.…”
Section: Discussionmentioning
confidence: 99%